PENGARUH PENDAPATAN KELUARGA DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA DI SMA NEGERI 5 PEKANBARU - Wati, Salistia; Sumarno, Sumarno; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to know the influence of familiy income and learning facilities on learning achievement of students. The population in this research is all of students grade X social and XI social at SMA Negeri 5 Pekanbaru as many as 325 students, and become a sample as many as 76 students. Research data using the question form and documentation. The analysis of the data used is a multiple linear regression. The result of research show that family income and learning facilities influences economics learning achievement of students at SMA Negeri 5 Pekanbaru, value of 1,468 and 1,562 with regression analysis Y=8,253+1,468+1,562. The contribution of family income and learning facilities on learning achievement of 39,5%.Keywords: Family income, learning facilities, learning achievement